The Right of Access to Public Information: Human Rights Issues, Transparency and Good Governance - Didier Yangonzela Liambomba (Constitutionale, 2023)
The right of access to information is based on both Article 19 of the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR), which guarantee everyone the right and freedom “to seek, receive and impart information and ideas” by any means of their choice. Article 24 of the Constitution of the Democratic Republic of Congo (DRC) guarantees the right to information in the following terms: “everyone has the right to information”. The effective manifestation of this right to information remains closely linked to the exercise of freedom of expression and opinion on any subject of public interest and its inevitable corollary, freedom of information. The effectiveness of the right to information also depends on citizens' participation in the nation's public life. A population well-informed by its government can fight against fake news and the spread of false rumors while promoting the fight against corruption and good governance. Accessing public information is one of the most important conditions for assessing the democratic management and openness of society to citizen participation. As an inalienable right, access to information is the foundation of a free, democratic and transparent society. The research was based on the legal approach and the comparative method. The former allowed the subject to be approached by grasping the quintessence of the various existing legal standards. The latter helped to compare the various internal and extra-internal legal instruments based on comparative law, particularly French law. This analysis also used the documentary technique and the free interview in the form of a chat with ordinary citizens or any other personality (civil society groups, journalists, entrepreneurs, national and local elected representatives, other professional, political and trade union groups, and civil servants).